(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Most of the research in Citrus hystrix uses ethanol and methanol as solvent for extraction, which is highly toxic. This may cause serious environmental and biological effects in case of residual solvent concentration. Synthesis process, in such cases, is also ecologically toxic. Green nanotechnology is a bio-inspired approach for engineering eco-friendly nanoformulations. Objectives: This research study aimed to explore antimicrobial effects of Citrus hystrix loaded silver nanoparticles prepared by green nanotechnology. Methods: The peels of Citrus hystrix was extracted using water, which is the greenest solvent. The silver nanoparticles were synthesised by the aqueous extract after phytochemical analysis. Synthesised nanoparticles was characterized to series of spectroscopic studies. After successful characterization, antibacterial and antifungal activities was determined by Agar plate method. Results: Aqueous extract of Citrus hystrix showed presence of tannins, flavonoids, alkaloids, and saponins. The synthesis of silver nanoparticles was confirmed by colour change from colourless to reddish brown colour. A broad peak with Absorption maxima (λmax) was observed at 455 nm indicating polydispersity. This phenomenon was also confirmed by the XRD and SEM. Meanwhile, stretching of C=O, C-H, C-C was confirmed by FT-IR. XRD also confirmed the (111) face-centred cubic plane at 37°. Antibacterial activity against Escherichia coli and antifungal activity against Aspergillus niger were promising. Conclusion: The synthesised silver nanoparticles exhibited excellent antibacterial and antifungal activity against Escherichia coli and Aspergillus niger respectively. This comprehensive research provides promising insight on synthesis of Citrus hystrix silver nanoparticles green nanotechnology.